The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1530-0277.2012.01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Liver Stiffness with Hepatic Expression of Pharmacokinetically Important Genes in Alcoholic Liver Disease

Abstract: In conclusion, CYPs and drug transporters seem to be induced in chronic alcoholics without irreversible liver damage but decline in case of manifest cirrhosis. Our study also suggests that noninvasive measurements of LS could be useful for pharmacokinetic predictions and individualized pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
(53 reference statements)
0
16
1
1
Order By: Relevance
“…This is in contrast to the previous pilot study that showed significant differences between KS of allografts with stable and impaired function but did not define and use criteria for reliable measurements [17]. It also clearly contrasts recent data obtained in liver where stiffness correlates well with liver function [30].…”
Section: Discussioncontrasting
confidence: 55%
“…This is in contrast to the previous pilot study that showed significant differences between KS of allografts with stable and impaired function but did not define and use criteria for reliable measurements [17]. It also clearly contrasts recent data obtained in liver where stiffness correlates well with liver function [30].…”
Section: Discussioncontrasting
confidence: 55%
“…), which may interfere with CYP expression and hepatic drug metabolism. Supporting this, the Heidelberg workgroup found reduced CYP2E1 expression in liver fibrosis, identified with liver stiffness elastography, as well as boosted CYP expression, drug metabolism, and subsequently increased, carcinogenic etheno-DNA adducts in (nonfibrotic) alcoholic liver disease [41, 42]. Therefore, the in-depth evaluation of CYP regulation in liver disease states is also of chief clinical relevance.…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, the observed increases of protein expression in this particular experimental setting might simply be too small to cause detectable activity changes in the flow cytometry approach. Irrespective of these uncertainties, drug transporters shall still have an impact on pharmacokinetics in alcoholics because other important drug transporters beside Pgp were also influenced (Figure ) and were reported to be slightly differentially expressed in alcoholics compared with healthy controls . The net functional consequences of these manifold slight upregulations of drug transporters are admittedly difficult to estimate, but clinical trials determining pharmacokinetics of selective Pgp substrates such as digoxin can clarify whether Pgp changes truly affect drug kinetics in chronic alcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have recently demonstrated that chronic alcoholics without pathologically increased liver stiffness (i.e. with absence of severe alcoholic liver disease) tend to exhibit higher hepatic messenger RNA (mRNA) expression of pharmacokinetically important genes compared with healthy controls . With respect to drug transporters, no definite data exist whether ethanol alters expression and activity of human drug transporters at pharmacological barriers such as the intestine despite convincing data from experiments with ethanol‐treated rats exhibiting increased intestinal efflux transporter expression and activity upon alcohol exposure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation